Rediscovery and redescription of the type of Philodryas laticeps Werner, 1900 and the taxonomic status of P. oligolepis Gomes, 1921 (Serpentes, Colubridae) - Zaher, Hussam; Scrocchi, Gustavo; Masiero, Roberta (Zootaxa, 2008)
Philodryas laticeps Werner, 1900 was previously known only from the holotype, which was believed to be lost during the World Wars. We found the holotype to be housed in the Museum für Naturkunde, Berlin and here redescribe it and report on three additional specimens from the collections of the Instituto Butantan, São Paulo and Museum für Naturkunde, Berlin. We conclude that Philodryas oligolepis Gomes, 1921 and P. affinis Müller, 1928 are junior synonyms of Philodryas laticeps Werner, 1900. All specimens share the presence of a black mucosa surrounding the larynx and trachea in the floor of the mouth and distal rows of middle sized spines disposed in a typical “V-shaped” configuration on the asulcate surface of the hemipenial body, two uniquely derived features absent in all other species of the genus Philodryas. Intraspecific variation of external morphology, hemipenes, and coloration are documented.